Recent evolution of a TET-controlled and DPPA3/STELLA-driven pathway of passive DNA demethylation in mammals - Christopher B. Mulholland (Nature Portfolio, 2020)
Active and passive demethylation pathways have been implicated in the genome-wide erasure of 5mC accompanying mammalian preimplantation development. Here the authors reveal a recently evolved, mammalian-specific pathway in which global hypomethylation is achieved by the coupling of active and passive demethylation.